Juegos verbales y expresión oral en niños de la Institución Educativa Inicial Jardín Piloto N° 179, Iquitos 2022 - Perez Vasquez, Ariana Janeth (2024)
The study investigation as a goal: Relate verbal games and oral expression of the children of the Pilot Garden Initial Educational Institution No. 179 of Iquitos 2022. Med at finding the relationship between the variables of study. The study population and sample consisted of 141 schoolchildren who were served by their teachers and recorded in observation guides, instruments validated by experts in due course, applying data collection instruments focused on collecting information related to the study variables. The research design was cross-sectional, bivariate, field, relational type of research. It is concluded by indicating that the Pearson correlation coefficient of 0.627 shows a moderate to high relationship between verbal games and oral expression in the children studied. This suggests that verbal games may be a significant factor in the development of oral expression skills in schoolchildren. Analysis of the scatter plot, which shows a positive sloping trend, reinforces this conclusion. It indicates that an increase in the practice of verbal games is associated with an improvement in oral expression, suggesting a potential causal relationship between these variables.